Cultural Literacy in Ethnoscience Learning: Perseption of Science Teacher Candidate - Agus Muliadi; Joni Rokhmat; Aliefman Hakim; AA Sukarso (Postgraduate Program, University of Mataram, 2024)
This study aims to explore the perceptions of prospective science teacher students regarding cultural literacy in science learning. This study is an exploratory research with research subjects as many as 28 biology education students. This research uses a research instrument in the form of a closed questionnaire with answers using a Likert scale and has been validated by experts. This research data was analyzed using quantitative descriptive statistics and inferential statistics of the t-test and Anova test. The results of this research are (1) male students have an average score of 3.00 in the Tall category and female students have an average score of 2.79 in the Tall category; (2) students from Mataram have an average score of 2.79 in the Tall category, West Lombok is 2.93 in the Tall category, Central Lombok is 2.95 in the Tall category, East Lombok is 2.88 in the Tall category , North Lombok at 2.78 in the Tall category; (3) students' perceptions of the indicator of understanding the value of diversity have an average score of 2.40 in the Low category, sensitivity to culture is 3.22 in the Tall category, and Interaction with culture is 3.23 in the Tall category; (4) there is no significant difference in the perceptions of male and female students regarding cultural literacy in ethnoscience learning as evidenced by a significance value of 0.384 which is greater than 0.05 (>0.05); (5) there is no significant difference in students' perceptions of cultural literacy in ethnoscience learning based on their region of origin as evidenced by a significance value of 0.914 which is greater than 0.05 (>0.05).